Religion in Secular Society : Fifty Years On - Wilson, Bryan R.; Edited by Bruce, Steve (United Kingdom Oxford University Press, 2016)
This is a new edition of 'Religion in Secular Society' by Bryan Wilson (1926-2004), a Fellow of All Souls College, Oxford for thirty years and one of the leading sociologists of religion of the twentieth century.
Include Index
Keywords: Church and the world -- Religion and sociology -- Secularism